Functional and perceptive differences between conventional and advanced ankle foot orthoses in community ambulators post-limb trauma: the injuries managed with advanced bracing of the lower extremity (IM ABLE) study - M. Jason Highsmith; M. Jason Highsmith; Rebecca M. Miro; Michael Kartel; Anita Ramrattan; Angela Courtade; Jeffrey T. Heckman; Jeffrey T. Heckman; Samuel L. Phillips; Shane R. Wurdeman; Thomas V. DiBello; Dwiesha L. England; et al. (Frontiers Media S.A., 2024)
IntroductionMany military service members and civilians suffer from lower extremity trauma. Despite recent advancements in lower limb bracing technology, it remains unclear whether these newer advanced braces offer improved comfort and functionality compared to conventional options. The IDEO (Intrepid Dynamic Exoskeletal Orthosis), a type of "advanced" orthosis was developed to assist in maintaining high functional performance in patients who have experienced high-energy lower extremity trauma and underwent limb salvage surgeries.MethodsA cross-sector multi-site initiative was completed to study the efficacy of advanced ankle foot orthoses (AFO) for lower limb trauma and injury compared to a conventional AFO. Following fitting, training, and accommodation, the subjects were assessed in each AFO system for mobility, self-reported function, safety and pain, and preference.ResultsThey preferred the advanced over the conventional AFO and the mobility and exertion perception improved with the advanced AFO with no difference in pain or overall health status scores.DiscussionThus, an advanced AFO is an option for trauma affecting the lower limb. Long-term studies are required to better understand the accommodation and learning process of using an advanced AFO.